2016
DOI: 10.3906/vet-1602-84
|View full text |Cite
|
Sign up to set email alerts
|

Circulating metabolic and reproductive hormone changes in laying hens kept under various heat-combating systems

Abstract: The objective of the present study was to observe the circulating metabolic, reproductive, and stress hormones in laying hen performance under different heat-combating systems (HCSs). A total of 500 White Leghorn pullets at 24 weeks of age were subjected to four HCSs, i.e. desert cooling (DC), water sprinkling (WS), time limit feeding (TLF), and ascorbic acid (AA) supplementation, at environmental temperatures from 32.30 to 40.80 °C with 76.40% relative humidity. Blood was collected before heat stress, at peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Low ovarian activity and egg production may also stem from alterations in neurotransmitter activity 24 , reduced blood flow to the ovary, and lower secretion of the hormones triiodothyronine, estrogen, progesterone, follicle-stimulating hormone, and luteinizing hormone 25 . Rozenboim et al 26 suggested that heat stress directly influences ovarian activity by reducing plasma levels of steroid hormones and expression of steroidogenic enzymes in follicles, which may prevent follicle development 27 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Low ovarian activity and egg production may also stem from alterations in neurotransmitter activity 24 , reduced blood flow to the ovary, and lower secretion of the hormones triiodothyronine, estrogen, progesterone, follicle-stimulating hormone, and luteinizing hormone 25 . Rozenboim et al 26 suggested that heat stress directly influences ovarian activity by reducing plasma levels of steroid hormones and expression of steroidogenic enzymes in follicles, which may prevent follicle development 27 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The serum was kept stored at −20°C for further analysis. For the detection of hormones, the methods were adopted as described elsewhere by Biswas, Mohan, and Sastry () and Anjum, Sandhu, Rahman, and Safdar (). Serum total T 3 and T 4 were quantified by the use of ELISA kits according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The serum was kept stored at −20°C for further analysis. For the detection of hormones, the methods were adopted as described elsewhere by Biswas, Mohan, and Sastry (2010) and Anjum, Sandhu, Rahman, and Safdar (2016…”
Section: Serum Hormonesmentioning
confidence: 99%